Notes on mating behaviour and a possible new host plant for megacyllene angulata (Fabricius, 1775) (cerambycidae, coleoptera) - Nascimento, Francisco Eriberto de L.L.; Mendes, Diego M.M.; Silva Neto, Alberto Moreira da (Papeis Avulsos de Zoologia, 2020)
The mating behavior of M. angulata (Fabricius, 1775) is described, illustrated and discussed. Additionally, we also comment on the possible new host plant of this species based on two plants (Luehea cymulosa Spruce ex Benth. (Malvaceae) and Doliocarpus dentatus (Aubl.) Standl (Dilleniaceae) on which copulation occurs. © 2020, Universidade de Sao Paulo. All rights reserved.